Environmental problems arising from the Dora industrial refinery complex site - قحطان هاشم جونه, م.م.; اركان ريسان عباس , أ.م.د (lark, 2020)
The current research focuses on the problem of the environmental impacts of the work of the industrial cycle refinery complex in the capital, Baghdad, represented by gaseous emissions, liquid and solid wastes, and visual and audio pollution, as due to many factors that come in the forefront of the issue of obsolescence and failure to implement plans for the continuous development and maintenance of the complex facilities, which are supposed To keep pace with the technical development of the oil industries in the world, and the research relied on two methods, namely the office study in addition to applying the questionnaire form to a sample of (400) respondents that resulted in reaching important results in terms of pollution levels emitted from the complex.